Prevalence of Malnutrition among School Children in Rural Area Of North Karnataka Region - Malpani, Ashok Kumar; Sarat, Srividya; V.H, Shivanand; Ade, Anju (Indian Journal of Pharmacy Practice)
Objective: The objective of the present study is to evaluate the level of malnutrition and the impact of households on the nutritional status of school children in a rural area of north karnataka region. Materials and methods: The study was a cross-sectional descriptive survey using a structured questionnaire which includes Anthropometric measurements height (H/A) and weight (W/A). Factors included: the number of children of 5 to 14 years of age in the family, occupation of the parents, family income, maternal education, type of residence (kacha or pucca) and children gender. Results: Two hundred and seventy school children representing a rural area of Raichur district, north karnataka were participated in the study. Reference standards used were those of WHO growth charts. The results showed the level of stunting and underweight in school children as per percentile standards from the WHO. Most of the boys and girls of the study fall under < 3rd percentile. Hence, malnutrition was significantly higher among the school children. The higher the level of the mother’s education, the lower the level of child’s underweight was observed. In the present study, growing children by and large are deprived of good nutrition on account of their poor socio-economic status, ignorance and lack of health promotional facilities. Conclusion: The study findings imply that efforts for redressing child under nutrition issues in rural areas should focus on factors associated with development outcomes such as family income, maternal education, and the creation of employment
Keywords: Malnutrition; Percentile; Socio-economic Factors; Anthropometry